Isolation and genotyping of Campylobacter species from kiwi (Apteryx spp.) in captivity: implications for transmission to and from humans. Issue 3 (4th May 2019) - On, SLW; Brett, B; Horan, S; Erskine, H; Lin, S; Cornelius, AJ
ABSTRACT: Aims: To investigate the presence of Campylobacter spp. in captive kiwi ( Apteryx spp.) and compare their genotypic profiles with those of human and animal origin, in order to assess their potential for zoonotic or zooanthroponotic transmission. Methods: Conventional selective enrichment and filter-based isolation methods were applied to isolate Campylobacter spp. from fresh faecal samples from 12 North Island brown kiwi ( Apteryx mantelli ) and one great spotted kiwi ( A. haastii ), housed in one of five different areas in a kiwi sanctuary in Christchurch, New Zealand. Isolates were identified using multiplex PCR and 16S rRNA gene sequencing. High-resolution rapid genotyping using multiplex ligation-dependant probe amplification-based binary typing (MBiT) was applied and profiles compared with similar results from 2, 165 Campylobacter spp. isolates contained in a database derived from human clinical, veterinary and environmental samples. Results: One isolate of C. jejuni, and one belonging to the C. lari phylogenetic group were recovered from faeces from two kiwi. High-resolution rapid genotyping by MBiT demonstrated these to be indistinguishable from isolates obtained previously from human cases of diarrhoea, and others from chicken, cattle, sheep and water. Conclusions: These data provide evidence for potential zoonotic or zooanthroponotic transmission of Campylobacter spp. in kiwi with implications for management of birds kept in captivity. We believe this is the first formal report of C. jejuni and a C. lari- like organism in kiwi. Abbreviations: MBiT: Multiplex ligation-dependant probe amplification-based binary typing